Serbia Public Expenditure and Financial Accountability Performance Report : Repeat Assessment - World Bank (Washington, DC, 2016)
A Public Expenditure and Financial accountability (PEFA) repeat assessment was conducted in the Republic of Serbia (RoS) between November 2014 and May 2015 by an independent team of experts, led by the World Bank (WB). The assessment was financed jointly by the Strengthening of Accountability and the Fiduciary Environment (SAFE) Trust Fund of the Swiss State Secretariat for Economic Affairs (SECO), the European Union Delegation to Serbia (EU Delegation) and WB. The period covered by this Assessment (2011-2013) was dominated by the challenges posed by the aftermath of the global economic recession which affected macro-fiscal performances. Notwithstanding these challenges PFM improvements can be observed in strengthening legislative framework, and Budget classification, multi-year fiscal planning, procurement and external audit. In other areas such as the composition of expenditure out-turn compared with originally approved budget, expenditures arrears, oversight of fiscal risk, and effectiveness of tax collection, predictability in the availability of funds, application of public sector accounting standards application and legislative scrutiny of annual budget law and final accounts, further work is needed to improve PFM performance.